Dose‐Dependent Acute Effects of Everolimus Administration on Immunological, Neuroendocrine and Psychological Parameters in Healthy Men. Issue 6 (31st May 2020) - Hörbelt, Tina; Kahl, Anna Lena; Kolbe, Frederike; Hetze, Susann; Wilde, Benjamin; Witzke, Oliver; Schedlowski, Manfred
Abstract : The rapamycin analogue everolimus (EVR) is a potent inhibitor of the mammalian target of rapamycin (mTOR) and clinically used to prevent allograft rejections as well as tumor growth. The pharmacokinetic and immunosuppressive efficacy of EVR have been extensively reported in patient populations and in vitro studies. However, dose‐dependent ex vivo effects upon acute EVR administration in healthy volunteers are rare. Moreover, immunosuppressive drugs are associated with neuroendocrine changes and psychological disturbances. It is largely unknown so far whether and to what extend EVR affects neuroendocrine functions, mood, and anxiety in healthy individuals. Thus, in the present study, we analyzed the effects of three different clinically applied EVR doses (1.5, 2.25, and 3 mg) orally administered 4 times in a 12‐hour cycle to healthy male volunteers on immunological, neuroendocrine, and psychological parameters. We observed that oral intake of medium (2.25 mg) and high doses (3 mg) of EVR efficiently suppressed T cell proliferation as well as IL‐10 cytokine production in ex vivo mitogen‐stimulated peripheral blood mononuclear cell. Further, acute low (1.5 mg) and medium (2.25 mg) EVR administration increased state anxiety levels accompanied by significantly elevated noradrenaline (NA) concentrations. In contrast, high‐dose EVR significantly reduced plasma and saliva cortisol as well as NA levels and perceived state anxiety. Hence, these data confirm the acute immunosuppressive effects of the mTOR inhibitor EVR and provide evidence for EVR‐induced alterations in neuroendocrine parameters and behavior under physiological conditions in healthy volunteers.